CODE – SWITCHING IN UNIVERSITY STUDENTS: A SIGN OF WEAKNESS OR LINGUISTIC STRENGTHS? - Zokirova Odina Shavkatjon qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
As the 21st century considered the period of developing digital technology, all school graduaters are preferring to learn languages to investigate new methods, approaches and techniques in each field of study. These students instead of stopping their learning at school, more of them are choosing to continue their studies in bachelor’s and master’s degrees . It is fact that, school pupils are entering the Universities by knowing at least 3 languages. These language speakers are becoming a multilingual society in university, where students often communicate using their first, second, and third languages equally in their daily communication. This phenomenon is known as code switching, which means fixing languages in speech, has become a common feature of student interaction in both inside and outside the classroom. While some teachers or parents are considering code switching a sign of insufficient language proficiency, others view it like a strong point of language learner along with an indicator of linguistic flexibility and cognitive strengths. The nature of code-switching among college students is examined in this article, along with its causes, purposes, and significance for learning second and third languages. The article makes the case that code-switching should not always be viewed as a weakness but rather as a sophisticated communicative technique that demonstrates multilingual competency by looking at linguistic research and classroom observations. Teachers can foster good attitudes toward multilingualism and improve language learning environments by having a better understanding of this phenomena.